Current Progress in Quinazoline Derivatives as Acetylcholinesterase and Monoamine Oxidase Inhibitors. Issue 28 (26th July 2021) - Rehuman, Nisha Abdul; Al‐Sehemi, Abdullah G.; Parambi, Della Grace Thomas; Rangarajan, T. M.; Nicolotti, Orazio; Kim, Hoon; Mathew, Bijo
Abstract: Among the N ‐containing heterocyclic compounds, quinazoline‐4‐(3H)‐one derivatives have been the center of attraction of medicinal and synthetic chemists due to their excellent versatility in biological activities that are witnessed by many approved drugs available in the market which contains quinazoline as main pharmacophore unit. This review mainly focuses the recent and current progresses in quinazoline derivatives as an acetylcholinesterase (AChE) and monoamine oxidase (MAO)‐B inhibitors. The review has leanings towards the molecular determinants and structure‐activity relationships (SAR) of quinazoline derivatives on AChE and MAO inhibitory potencies. Abstract : Quinazolines are fused bicyclic heterocyclic compounds containing two nitrogen atoms represent a privileged scaffold for the inhibition of monoamine oxidase and acetylcholinesterase. The current review focus on the detailed structure requirement of on quinazoline heterocyclic ring as the inhibitors of MAO−B and AChE.